Systematic review and meta-analysis of in vitro efficacy of antibiotic combination therapy against carbapenem-resistant Gram-negative bacilli - Scudeller, Luigia; Righi, Elda; Chiamenti, Margherita; Bragantini, Damiano; Menchinelli, Giulia; Cattaneo, Paolo; Giske, Christian G.; Lodise, Thomas; Sanguinetti, Maurizio; Piddock, Laura J.V.; Franceschi, François; Ellis, Sally; et al. (International journal of antimicrobial agents, 2021)
•In vitro models may inform on the efficacy of antibiotic regimens against carbapenem-resistant Gram-negative bacilli.•High or moderate synergism was shown for polymyxin/rifampicin vs. A. baumannii and polymyxin/fosfomycin vs. K. pneumoniae.•High or moderate synergism was also shown for imipenem/amikacin vs. P. aeruginosa.•Combinations including old antibiotics appear promising, while high-quality studies on novel antibiotics are lacking.•Correctly designed in vitro studies may highlight potential synergies to test in human trials or to optimise further tests. The superiority of combination therapy for carbapenem-resistant Gram-negative bacilli (CR-GNB) infections remains controversial. In vitro models may predict the efficacy of antibiotic regimens against CR-GNB. A systematic review and meta-analysis was performed including pharmacokinetic/pharmacodynamic (PK/PD) and time–kill (TK) studies examining the in vitro efficacy of antibiotic combinations against CR-GNB [PROSPERO registration no. CRD42019128104]. The primary outcome was in vitro synergy based on the effect size (ES): high, ES ≥ 0.75, moderate, 0.35 < ES < 0.75; low, ES ≤ 0.35; and absent, ES = 0). A network meta-analysis assessed the bactericidal effect and re-growth rate (secondary outcomes). An adapted version of the ToxRTool was used for risk-of-bias assessment. Over 180 combination regimens from 136 studies were included. The most frequently analysed classes were polymyxins and carbapenems. Limited data were available for ceftazidime/avibactam, ceftolozane/tazobactam and imipenem/relebactam. High or moderate synergism was shown for polymyxin/rifampicin against Acinetobacter baumannii [ES = 0.91, 95% confidence interval (CI) 0.44–1.00], polymyxin/fosfomycin against Klebsiella pneumoniae (ES = 1.00, 95% CI 0.66–1.00) and imipenem/amikacin against Pseudomonas aeruginosa (ES = 1.00, 95% CI 0.21–1.00). Compared with monotherapy, increased bactericidal activity and lower re-growth rates were reported for colistin/fosfomycin and polymyxin/rifampicin in K. pneumoniae and for imipenem/amikacin or imipenem/tobramycin against P. aeruginosa. High quality was documented for 65% and 53% of PK/PD and TK studies, respectively. Well-designed in vitro studies should be encouraged to guide the selection of combination therapies in clinical trials and to improve the armamentarium against carbapenem-resistant bacteria.